Intelligent Robotics - Mehmi, Tushar; Rohdia, Taruna; Yadav, Upender (IJRDO -Journal of Computer Science Engineering, 2015)
Robotics has always been a fertile inspiration paradigm for AI research, frequently referred to in its literature, in particular in the above topics. The ambition of this paper is to review revival. It proposes an overview of problems and approaches to autonomous deliberate action in robotics. The paper advocates for a broad understanding of deliberation functions. It presents a synthetic perspective on planning, acting, perceiving, monitoring, goal reasoning and their integrative architectures, which is illustrated through several contributions that addressed deliberation from the AI– Robotics point of view.